BIOLOGICAL EFFECT OF H. ERINACEUS FRUITBODIES POWDER ON FERTILITY OF D. MELANOGASTER - Bilokon, S.; Alieksieieva, T.; Tkachenko, F. (Sworld-Us Conference proceedings, 2022)
The edible mushroom H. erinaceus has recently attracted the special attention of researchers due to its primary and secondary metabolites and their possible medicinal applications. The fruitbodies and mycelia of H. erinaceus have been reported to produc